ANTHRAX, PENYAKIT YANG MUNCUL KEMBALI DI BEBERAPA TEMPAT DI INDONESIA - Simanjuntak Gindo M; Salma Ma'roef; Hasyimi Hasyimi; Widarso HS; Wilfried H. Purba (JURNAL LITBANG PROVINSI JAWA TENGAH, 2003)
Anthrax disease is a member of zoonoses group, causesd by Bacillus anthracis, geographically distributed in nine provinces of Indonesia: Jambi, Jakarta, West Java, Central Java, West Nusatenggara, East Nusatenggara, South Sulawesi, Southeast Sulawesi and Irian Jay a. However, during the last decade, there is no reported case of anthrax from Jambi, Jakarta, and lrian Jaya, but the risk of re-emerging of anthrax have to be considered. Beside anthrax in human, this disease can be found also in cattle, buffalo, horse, goat, sheep and ostrich bird. Anthrax surveillance in livestock during the year of 1996- 2001 period showed that anthrax always re-emerged except in 1998. In Central Java, its re-appeared in 1996, 1997 and 1998. In West Nusatenggara anthrax re-emerged yearly except in 1998 and in 2000. In East Nusatenggara as well as in Southeast Sulawesi anthrax used to be re-emerged yearly. In South Sulawesi, anthrax only re-appeared in 1998 and in 2000. The number of anthrax in animal from all anthrax endemic areas were 173 cases in 1996, 251 cases in 1997, 17 cases in 1998, 273 cases in 1999, 332 cases in 2000 and 228 cases in 2001. Anthrax among the human population in Indonesia were 51 cases in 1996, without any death as well as in 1997 were 24 cases, in 1998 were 20 cases, and in 2000 were 34 cases. One death out of 55 cases was occurred in 1999 which happened in Manggarai district, East Nusatenggara province, and four death out of 23 cases were occurred in 2001 that happened in Bogor district, West Java province.